Footprints of the self in Historia del pelo (A history of hair) by Alan Pauls - Martínez M., María Luisa (2019)
Historia del pelo by Alan Pauls (2010) reveals the mysterious connections between the great political stories and the seemingly irrelevant small everyday events that make up life. The story of the Argentinian dictatorship is expresses from a self-fictional narrative where an insignificant element, hair, acquiresan iconic value. It represents an era, a style, a social and even ethnical space. The humanity inscribed in hair represents the political character of culture, which imposes a certain era or space, but also the proximity to unrecognisable lives, outside the great historical stories. The characters in Pauls’ novel show a path marked by loneliness, illness, and the threat of death. The traces that hair imprints on the body are inscribed as the tale of a subjective memory that is reflected in the presence of the animal figure, the non-person, whichaddresses and questions us.